SECURITY STRATEGY FOR THE IMPLEMENTATION OF THE 2024 GENERAL ELECTION AT THE STATE DETENTION CENTRE CLASS I MEDAN - Fadilla, Djian; Kurniawan, Andi (Universitas Nusa Cendana, 2025)
This study aims to analyze the security strategy for the implementation of the 2024 General Election at the Medan Class I State Detention Center, as well as to identify inhibiting factors that affect the smooth running of security. The implemented security strategy includes five dimensions of strategy theory: position, perspective, planning, pattern, and tactics. The results showed that the security strategy was designed with a comprehensive approach through risk mapping, division of surveillance zones, and cross-agency cooperation such as KPU, police, and TNI. However, several inhibiting factors emerged from each dimension, including overcrowding, voter identity verification, suboptimal inter-agency coordination, limited human resources, and challenges in managing the flow of officers and logistics. This study provides recommendations for strengthening inter-agency coordination and optimizing resources to ensure the implementation of the 2024 General Election in Medan Class I Detention Centers runs safely and smoothly. Keywords: Strategy; Security; Election